Investigation of multinucleation and apoptosis of macrophages of BCG-infected mice and their production of cathepsins and matrix metalloproteinases - D. А. Il’in (Сибирский научный медицинский журнал, 2024)
The relevance of the study of the role of macrophages and their multinucleated forms in the pathogenesis of tuberculous granulomatosis is determined by its wide prevalence, the presence of severe socio-economic consequences of its morbidity and necrotic complications, which are based on the high destructive potential of macrophages associated with the role of hydrolases in the degradation of extracellular matrix components. Aim of the study was to investigate the features of the multinucleation, apoptosis and expression of a number of hydrolases in macrophages of BCG-infected mice. Material and methods. The intensity of macrophage multinucleation and apoptosis, the peculiarities of their expression of matrix metalloproteinases (MMP-1, MMP-9), catepsins (CatB, CatD), caspase-3, and p53 protein were studied in peritoneal cells cultures of intact and BCG-infected BALB/c mice. Results. The number of multinucleated macrophages increased according to the terms of the experiment, having a maximum value for 3 months of observation, but after 2 months almost reaching this level. The realization of apoptosis, multinucleation of macrophages had a complex character, determining the composition of their subpopulations. The dynamics of the expression of the studied hydrolases by macrophages indicated their unequal role in tissue necrosis at various stages of granulomogenesis. The high functional ability of multinucleated macrophages to produce hydrolases of certain types is shown. Intense expression of MMP-1 in the early stages of granulomogenesis and its maximum value, as well as CatD expression for 3 months, and strong expression of MMP-9 for 6 months were noted. Conclusions. Stimulation of plastic processes in macrophages under conditions of BCG-granulomatosis determines the formation of multinucleated macrophages with high functional potential and intensive expression of hydrolases by macrophages for 2 and 3 months of granulomogenesis. These are periods of high risk of necrotic complications of tuberculous granulomatosis, which should be taken into account when developing methods for their prevention and therapeutic correction.